Does COMT val158met polymorphism influence P50 sensory gating, eye tracking or saccadic inhibition dysfunctions in schizophrenia?. (30th December 2016) - Demily, Caroline; Louchart-de-la-Chapelle, Sandrine; Nkam, Irène; Ramoz, Nicolas; Denise, Pierre; Nicolas, Alain; Savalle, Caroline; Thibaut, Florence
Abstract: Three electrophysiological endophenotypes are routinely studied in schizophrenia (SCZ): smooth pursuit eye movement (SPEM) dysfunction, deficits in P50 auditory-evoked potential inhibition, and saccadic inhibition deficits. The current study aimed to investigate the relationship between the COMT val158met polymorphism and these three endophenotypes. One hundred four SCZ patients (DSM-IV-R criteria) and 89 healthy controls were included in this study. P50 auditory-evoked potential inhibition, antisaccade paradigm and SPEM were analyzed. All individuals were genotyped for the COMT val158met. SCZ patients showed a higher rate of deficits measured by the SPEM, antisaccade and P50 inhibition paradigms without association with COMT val158met. However, in our control group, we have found an association between the Val polymorphism and the smoking status. More importantly, we have found a higher accuracy of saccades during the predictive pursuit task associated to the Met polymorphism in controls but not in SCZ patients who were receiving antidopaminergic medications. This result is in line with the hypothesis of the relationship between the Met polymorphism of the COMT gene, a higher level of dopamine in the prefrontal cortex and the role of the fronto-cerebellar loop in smooth predictive pursuit. Highlights: Patients with schizophrenia show a higher rate of deficits measured by the SPEM, antisaccade and P50 inhibition paradigms. A higher accuracy of saccades during the predictive pursuit task associated is with the Met polymorphism in controls subjects. The COMT Val158Met polymorphism does not seem to be involved in these deficits observed in schizophrenia.